Inventory Management Practices and Service Delivery of Healthcare Facilities in Ilocos Norte Philippines - Eric S Parilla; Jocelyn Evangelista; Roselie Aurelio; Charliemaine Bullalayao (Research Synergy Press, 2022)
The study investigates the relationship between inventory management practices and service delivery. The study participants were the 16 healthcare facilities in Ilocos Norte and 80 patients, and they were chosen using a convenience sampling technique. The research used a quantitative research design and a casual research approach to measure the degree of relationship between the independent and dependent variables. Based on the findings of the study, there were five inventory management practices observed for the study—pharmacy premises and storage, drug information, safety and security, personnel and stock control, and monitoring. On the other hand, as service quality, hospitals have four categories. These are hospital admissions, care and treatment, hospital environment and facilities, and hospital discharge. Personnel and stock control and monitoring are significantly correlated to service quality Implications, conclusions, and recommendations were also provided in the study.